Deletion of Uncoupling Protein‐2 reduces renal mitochondrial leak respiration, intrarenal hypoxia and proteinuria in a mouse model of type 1 diabetes. (15th March 2018) - Friederich‐Persson, M.; Persson, P.; Hansell, P.; Palm, F.
Abstract: Aim: Uncoupling protein‐2 (UCP‐2) can induce mitochondrial uncoupling in the diabetic kidney. Although mitochondrial uncoupling reduces oxidative stress originating from the mitochondria and can be regarded as a protective mechanism, the increased oxygen consumption occurring secondarily to increased mitochondria uncoupling, that is leak respiration, may contribute to kidney tissue hypoxia. Using UCP‐2 −/− mice, we tested the hypothesis that UCP‐2‐mediated leak respiration is important for the development of diabetes‐induced intrarenal hypoxia and proteinuria. Methods: Kidney function, in vivo oxygen metabolism, urinary protein leakage and mitochondrial function were determined in wild‐type and UCP‐2 −/− mice during normoglycaemia and 2 weeks after diabetes induction. Results: Diabetic wild‐type mice displayed mitochondrial leak respiration, pronounced intrarenal hypoxia, proteinuria and increased urinary KIM‐1 excretion. However, diabetic UCP‐2 −/− mice did not develop increased mitochondrial leak respiration and presented with normal intrarenal oxygen levels, urinary protein and KIM‐1 excretion. Conclusion: Although functioning as an antioxidant system, mitochondria uncoupling is always in co‐occurrence with increased oxygen consumption, that is leak respiration; a potentially detrimental side effect as it can result in kidney tissue hypoxia; an acknowledged unifying pathway to nephropathy. Indeed, this study demonstrates a novel mechanism in which UCP‐2‐mediated mitochondrial leak respiration is necessary for the development of diabetes‐induced intrarenal tissue hypoxia and proteinuria.